Commodity futures impact on equity funds portfolios - Mc Guire,Oscar (2015)
In the light of the latest decade of structural change and growth in trade on the commodity markets it is natural to ask the question: Is it worth adding commodity futures to your portfolio? The objective of this paper is to find out if commodity futures does or does not add to the performance of portfolios consisting of equity funds. The theory used is basic portfolio theory, with Sharpe's ratio as the measure of performance. I simulate real time portfolio optimization on given data with expected returns calculated with 60 months historical data. The results ex-ante show a great enhancement of the Sharpe's ratio if adding commodity futures to a equity funds portfolios. The results also indicates that a less diversified portfolio gains more by adding the commodity futures, than does a well diversified one. Ex-post results, however, show a negative effect of adding commodity futures to both a well diversified portfolio and a less diversified one. My interpretation of this result is that, during a tumultuous decade, the method of calculating expected return with 60 months equally weighted averages do not yield sufficient precision in the forecasts
Keywords: Commodity futures; Sharpe's ratio; equity funds; sector funds; portfolio optimization.